Becoming a person from Mbya Guarani perspective (Misiones Province, Argentina) - Remorini, Carolina (2012)
The aim of this paper is to describe and discuss some results from an ethnographic research on Argentinian Mbya communities focused on representations and practices related to childrearing and development during the first stages of life course. Firstly, I describe Mbya lingüistic categories, representations and values about growth and development, focusing on processes and events which allow children to be transformed into persons. Mitã ñemongakuaa is the Mbya language expression used to refer to rearing practices; literally, it means “to make a child grow”. Being “kakuaa” , the term used to refer to children´s growth and development which is considered by Mbya people as a cultural and not natural process. In this sense, kakuaa means the achievement of certain socially recognized skills and attributes which makes the transition between life stages possible, bringing a change in children’s status. Therefore, being a “Mbya” is a status that is not achieved by birth but only when the personal name (sacred name) is given to the child. In this sense, one of the most important transitions in life course, which allows children to become persons, is the giving name ceremony called Ñemongarai. Secondly, I present some aspects of Mbya parental ethnotheories about childrearing and children´s growth and development. I specially analyze motor function as a central indicator of growth and health, describing daily practices oriented to promote movement as well as the beliefs and knowledge that justify them. Finally, based on that, I stress the close relationship among movement, children´s health, personhood and identity notion from Mbya perspective